The economics of corporate governance: Beyond the Marshallian firm - Garvey, Gerald T.; Swan, Peter L. (Journal of Corporate Finance, 1994)
It is now customary to view the corporation as nexus of explicit and implicit contracts. Governance determines how the firm's top decision makers (executives) actually administer such contracts. We survey recent theory and evidence on executive behaviour and incentives and reject the standard assumption of shareholder-wealth-maximisation, either in its strict sense or in the sense implied by standard principal-agent models. Explanations for this state of affairs as an inefficient, rent-seeking outcome are contrasted with efficiency explanations, particularly those that explicitly consider the diverse claims of employees, customers, and suppliers as well as those of investors.